Strategi Corporate Communication PT Amerta Indah Otsuka dalam membangun Customer Experience melalui Otsuka Factory Visit Sukabumi - Yohanes Tumpak Panggabean; David Rizar Nugroho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by changes in corporate communication in the digital era, which require companies not only to deliver information but also to create meaningful experiences for the public. PT Amerta Indah Otsuka, through the Otsuka Factory Visit Sukabumi program, implements an open factory and edutainment-based corporate communication strategy to build customer experience. This study aims to analyze the corporate communication strategy of PT Amerta Indah Otsuka based on Paul Argenti’s theory. This research used a descriptive qualitative approach through in-depth interviews, observation, literature study, and documentation. The results show that PT Amerta Indah Otsuka delivers educational, interactive, and consistent messages regarding product quality, production processes, and company philosophy. Otsuka factory visit creates a positive customer experience that increases visitors’ understanding, trust, emotional engagement, and positive perceptions toward the company and its products.